Morphological and functional changes in mycelium and mycorrhizas of Tuber borchii due to heat stress. (October 2017) - Leonardi, Pamela; Iotti, Mirco; Donati Zeppa, Sabrina; Lancellotti, Enrico; Amicucci, Antonella; Zambonelli, Alessandra
Abstract: Tuber borchii is an ectomycorrhizal ascomycete with a wide ecological range, which forms valuable fruit bodies (truffles). The effect of heat stress on the growth and morphology of ectomycorrhizas and mycelia of 11 T. borchii strains of different geographical and ecological provenance was evaluated. Mycelia and T. borchii -colonized plants were differentially grow at 22 °C, 28 °C and 34 °C. Further, the expression of two genes involved in stress response was also analysed in strains showing a different growth response to the high temperatures. Four out of 11 strains were classified as tolerant to heat stress based on their ability to grow and form mycorrhizas at 28 °C as at 22 °C. Only one strain seemed to show a high-temperature induced quiescence and survived after exposure at 34 °C. The expression of the genes considered in this work seems to be related to the level of heat stress tolerance in a strain.